2016
DOI: 10.3390/nu8100652
|View full text |Cite
|
Sign up to set email alerts
|

Defining Conditions for Optimal Inhibition of Food Intake in Rats by a Grape-Seed Derived Proanthocyanidin Extract

Abstract: Food intake depends on homeostatic and non-homeostatic factors. In order to use grape seed proanthocyanidins (GSPE) as food intake limiting agents, it is important to define the key characteristics of their bioactivity within this complex function. We treated rats with acute and chronic treatments of GSPE at different doses to identify the importance of eating patterns and GSPE dose and the mechanistic aspects of GSPE. GSPE-induced food intake inhibition must be reproduced under non-stressful conditions and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
(83 reference statements)
1
17
0
Order By: Relevance
“…Working with doses around 500 mg GSPE/kg b.w., a non-dietary dose, we showed that a dose of least 350 mg GSPE/kg b.w. is necessary to obtain satiating effects simultaneously to lipolytic action after 8–10 days of subchronic treatment [ 29 ]. Bao and colleagues proposed a minimum dose of 250 mg/kg, administered for 16 weeks, to obtain effects on body weight and also satiety, in a Diabetes Mellitus 1 model [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working with doses around 500 mg GSPE/kg b.w., a non-dietary dose, we showed that a dose of least 350 mg GSPE/kg b.w. is necessary to obtain satiating effects simultaneously to lipolytic action after 8–10 days of subchronic treatment [ 29 ]. Bao and colleagues proposed a minimum dose of 250 mg/kg, administered for 16 weeks, to obtain effects on body weight and also satiety, in a Diabetes Mellitus 1 model [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing all the considered aspects regarding the different administration time points of a GSPE dose of 500 mg/kg b.w., we can define the most optimal approach for using GPSE as an agent to avoid unhealthy states related to obesity. We have previously discarded the use of higher doses because they can produce negative effects [ 29 ], some of them related to desensitization to enterohomone signaling [ 40 ]. Dietary doses need to be used from the beginning of the challenge to produce the most effective results [ 7 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system, the level of GLP-1 in plasma was elevated by giving 1 g GSPE/kg to fasting rats [93]. GLP-1 is a peptide hormone coded by the human glucagon gene Fig.…”
Section: Reduce Food Intakementioning
confidence: 99%
“…Serrano et al showed that a dose of 500 mg/kg bw of a grape-seed proanthocyanidin extract (GSPE) was able to limit food intake [22], modify enteroendocrine hormone secretions [23], and decrease gastric emptying in female rats, thus inducing a satiating effect [24]. Moreover, the authors suggested that GSPE acts on food intake and body weight through vagal GLP-1 receptor (GLP-1R) activation on the hypothalamic centre of food intake control and GLP-1 production in the intestine [25]. Similarly, puerarin, a dietary isoflavone, improves glucose homeostasis in obese diabetic mice and protects pancreatic β-cell survival by mechanisms that involve the activation of GLP-1R signaling and downstream targets [26].…”
Section: Introductionmentioning
confidence: 99%